Pedagogia Sistêmica e suas contribuições: Um olhar para as relações e inter-relações entre família e escola no contexto de complexidade educacional - SOCOLOSKI, DIENIFFER (2022)
To develop the present study, it was established as a general objective to understand the contributions of systemic pedagogy in family and school relationships based on family dynamics. The study is qualitative in nature, characterized as action research based on the methodology of Creative Eco-training Projects (PCE) (TORRE; ZWIEREWICZ, 2009), based on complexity. The research field was developed in a public institution at the Elementary School level, in the municipality of Guarapuava, PR. For data collection, meetings were held based on the methodology of the Creative Ecoformer Projects (PCE), instruments such as: Conversation circle; field diary and online questionnaire were essential to achieve the proposed objectives. Among the authors used, Morin (2000, 2002, 2005,); Hellinger (2009, 2015); Francke (2006, 2009); Vilagines (2009, 2016); Guedes (2015), Torre (2008), Torre and Zwierewicz (2009), Moraes (2010); Rosset (2014); Minuchin (1982, 1988); among others that were fundamental for the development and discussions of the research. The sample consists of 10 (ten) family members of children who were enrolled in the initial grades of elementary school during the 2020 school year. 5 (five) professionals from the educational institution were also part of the sample, two of which were elementary school teachers, director and a supervisor. Data analysis will be based on the narratives of the meetings, on the observations made and noted in the researcher's logbook and through the questionnaire applied. The result achieved with the research based on the narratives made it possible to have a very broad view of the contributions of systemic pedagogy from the point of view of family members, teachers and the potential that this new knowledge can offer for relationships. Systemic knowledge made it possible to reconnect bonds that were fragile and to re-signify lived experiences, resulting in a movement of self-knowledge and belonging. Eco-training allowed a new way of thinking about life beyond individual needs, causing the participants to change their attitude towards the problematic relationship between family and school, once they understood that the path to solution depended on a collaborative behavior between the systems.